'Just stuff yourself': Identifying health‐promotion strategies from the perspectives of adolescent boys from disadvantaged neighbourhoods - Eva Lems; Femke Hilverda; Jacqueline E. W. Broerse; Christine Dedding (Wiley, 2019)
Abstract Context The prevalence of overweight and obesity among adolescents has risen dramatically in the last decade, disproportionally affecting adolescents from disadvantaged neighbourhoods. Adolescent boys from disadvantaged neighbourhoods are hard to reach for health promotion. Objective This study aims to understand perceptions of health and health‐promotion strategies among adolescent boys from disadvantaged neighbourhoods in order to identify opportunities for health promotion that are better tailored to their needs. Methods A qualitative, participatory research approach was used. Sixty‐three adolescent boys (aged 12‐18) were recruited from disadvantaged neighbourhoods in Amsterdam, the Netherlands. Semi‐structured interviews, participant observations and co‐creation sessions were conducted. Data were analysed using ethnographic content analysis. Results Boys associate the consumption of large portions of unhealthy foods, especially meat, with masculinity and autonomy. Buying junk food is an important part of their social lives. According to boys, current health promotion does not fit their needs. They stress that entertaining activities, humour and short‐term benefits of healthy choices must be central to health promotion. Some differing interests in health promotion appear between boys, but all boys plead for cheap, satisfying, tasty and healthy food options in their neighbourhoods. Conclusions Adolescent boys from disadvantaged neighbourhoods do see opportunities for health promotion. There is an emerging acceptance of boys taking care of their body and health, but the social norm of unhealthy consumption dominates. For health promoters, it is vital to gear health messages to who the boys are and wish to be, especially in relation to their peers.